Adolescents’ diets and aspirations in Surkhet, Nepal: Food consumption, task allocation, and future aspirations - Patwardhan, Sharvari; Chakrabarti, Suman; Neupane, Sumanta; Chauhan, Alka; Banerjee, Archis; Scott, Samuel P.; Ranathunga, Thilanka; Konapur, Archana; Menon, Purnima (CGIAR Initiative on Transforming Agrifood Systems in South Asia, 2023)
The Transforming Agrifood Systems in South Asia (TAFSSA) district agrifood systems assessment aims to provide a reliable, accessible, and integrated evidence base that links farm production, market access, dietary patterns, climate risk responses, and natural resource management with gender as a cross-cutting issue in rural areas of Bangladesh, India, and Nepal. It is designed to be a multi-year assessment. The survey was conducted only in households with adolescents (10-19 years of age). Adolescents and their behaviors are important when studying food systems because current practices and experiences can have long-term, intergenerational consequences. Using data collected in March-April 2023, this data note describes adolescents’ diets and future aspirations. This is one of a set of data notes that, together, provide a holistic picture of the agrifood system in the district.